Student’s Mathematics Creative Thinking Skills in Terms of Logical Mathematical Intelligence - Aini1, Afifah Nur; ., Sunardi; ., Slamin; ., Hobri (International Journal of Scientific Research and Management (IJSRM), 2017)
The objective of this study is to describe the skills of creative thinking in terms of logical mathematicalintelligence, by qualitative approach. Instruments used were questionnaires, tests, documentation, andinterviews. 54 students of class XI, MA Al-Misri were given a type of multiple intelligencesquestionnaire. 14 students who have logical mathematical intelligence predominant chosen as the subjectof research. The first test was given to determine the logical mathematical intelligence, then analyzed. Theanalysis showed consecutively 12; 8; 5; 3; and 1 subject(s) who has the characteristics classify, compare,perform basic numerical operations, deductive and inductive reasoning, and hypothesis formation andtesting. Next, each subject was chosen for each those characteristics. Open ended question was given forthe second test to describe student’s creative thinking skills. Based on data analysis, it was found that thesubjects with the characteristics classify, compare, perform basic numerical operations, deductive andinductive reasoning generally fulfill the components of creative thinking: problems sensitivity, fluency,flexibility and elaboration; and subject with characteristics of hypothesis formation and testing fulfill thefour components later and novelty